Three new species of Horismenus Walker (Hymenoptera: Eulophidae) associated with seed pods of Pithecellobium dulce (Fabaceae) - Pikart, Tiago G.; Costa, Valmir A.; Hansson, Christer; Zanuncio, José C.; Serrão, José E. (Zootaxa, 2015)
Horismenus abnormicaulis sp. nov., H. patensis sp. nov. and H. zuleidae sp. nov. (Hymenoptera: Eulophidae), all authored by Pikart, Costa & Hansson, are described from material obtained from seed pods of Pithecellobium dulce (Roxb.) Benth. (Fabaceae) collected in Northeastern Brazil. The seed pods were infested with larvae of Coleoptera (Chrysomelidae (Bruchinae) and Curculionidae). The associations of the Horismenus species and the beetle larvae have not been established. Morphological similarities between these new species and previously described species with host known suggest that H. patensis and H. zuleidae are primary parasitoids of Bruchinae, whereas H. abnormicaulis may act as a hyperparasitoid on other Horismenus species. The three species are compared with similar species of Horismenus.